2016
DOI: 10.1007/s40620-016-0334-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of denosumab in osteoporotic hemodialysed patients

Abstract: Our pilot experience highlights the safety and efficacy of denosumab in the treatment of osteoporosis in HD patients, potentially supporting its use to reduce the burden of fractures in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…Our patients' response to denosumab (decrease Ca level and increase iPTH level) was similar to several studies reported in ESRD patients [7,8,10,[15][16][17]. The transient surge of iPTH level in Patient 2 is most likely caused by a compensatory mechanism.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our patients' response to denosumab (decrease Ca level and increase iPTH level) was similar to several studies reported in ESRD patients [7,8,10,[15][16][17]. The transient surge of iPTH level in Patient 2 is most likely caused by a compensatory mechanism.…”
Section: Discussionsupporting
confidence: 88%
“…Patient's dialysate calcium bath was increased from 2.5 to 3.5 mEq/L and calcitriol 1 mcg daily treatment was initiated for hypocalcemia [15]. A retrospective study by Festuccia et al showed improvement in bone metabolism with denosumab in 12 hemodialysis patients without significant safety concerns over 24 months [8]. They observed a decrease in average serum Ca: 9 mg/dL at baseline, 8.1 mg/dL at 3 months, 9.4 mg/dL at 6 months, 9 mg/dL at 9 months, 9.8 mg/dL at 12 months, 8.9 mg/dL at 15 months, 9.2 mg/dL at 18 months, 9.3 mg/dL at 21 months, and 9.1 mg/dL at 24 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of concern, however, precipitating profound and prolonged hypocalcaemia resulting in seizures, cardiac arrhythmias and laryngospasm post‐denosumab administration in patients with CKD have been reported . Although there are no standardised and proven clinical recommendations to prevent this complication, evidence from small studies and expert opinion has recommended adequate vitamin D stores prior to the commencement of denosumab, with careful monitoring and supplementation of calcium as required post‐dose, especially within the first few weeks following its administration . Anecdotally, some centres now avoid the use of denosumab in patients with CKD stages 4–5.…”
Section: Bone Health In Patients With Chronic Kidney Disease–mineral mentioning
confidence: 99%
“…[55][56][57][58] Although there are no standardised and proven clinical recommendations to prevent this complication, evidence from small studies and expert opinion has recommended adequate vitamin D stores prior to the commencement of denosumab, with careful monitoring and supplementation of calcium as required post-dose, especially within the first few weeks following its administration. [58][59][60][61] Anecdotally, some centres now avoid the use of denosumab in patients with CKD stages 4-5. Thus, although its non-renal pharmacokinetics are appealing for use in CKD, its role is yet to be fully defined for these patients, and risk of hypocalcaemia in patients with CKD remains a concern.…”
Section: Denosumabmentioning
confidence: 99%